2012
DOI: 10.1093/toxsci/kfs100
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Induced by Sertraline, an Antidepressant Agent

Abstract: Sertraline, a selective serotonin reuptake inhibitor, has been used for the treatment of depression. Although it is generally considered safe, cases of sertraline-associated liver injury have been documented; however, the possible mechanism of sertraline-associated hepatotoxicity is entirely unknown. Here, we report that mitochondrial impairment may play an important role in liver injury induced by sertraline. In mitochondria isolated from rat liver, sertraline uncoupled mitochondrial oxidative phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 54 publications
(52 reference statements)
7
59
0
4
Order By: Relevance
“…Although it is generally considered safe, acute liver failure due to sertraline use has been documented [91][92][93][94][95][96][97][98][99]. Sertraline was demonstrated to be toxic in primary rat hepatocytes and human HepG2 cells; mitochondrial dysfunction and apoptosis are the underlying mechanisms [100,101]. Besides mitochondrial dysfunction and apoptosis, ER stress was found to contribute to sertraline's liver toxicity (SC and LG, unpublished data).…”
Section: Anti-depression Drugsmentioning
confidence: 99%
“…Although it is generally considered safe, acute liver failure due to sertraline use has been documented [91][92][93][94][95][96][97][98][99]. Sertraline was demonstrated to be toxic in primary rat hepatocytes and human HepG2 cells; mitochondrial dysfunction and apoptosis are the underlying mechanisms [100,101]. Besides mitochondrial dysfunction and apoptosis, ER stress was found to contribute to sertraline's liver toxicity (SC and LG, unpublished data).…”
Section: Anti-depression Drugsmentioning
confidence: 99%
“…Experimental evidences indicate that mitochondria represent a critical and preferred target for the action of drugs and toxins. The toxic effects on mitochondria can occur through direct and indirect mechanisms, leading to mitochondrial dysfunction such as changes in electron transport and oxidative phosphorylation, in inner mitochondrial membrane permeability, calcium transport, and the oxidative state as well as a series of other events that deplete ATP (Nadanaciva et al, 2007;Dykens et al, 2008;Castanha-Zanoli et al, 2012;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the mode of death for acetaminophen's liver toxicity is caspase-independent apoptosis, initiated by activation of PARP-1 [13][14][15]. The widely used antidepressant, sertraline was shown to cause to apoptosis and mitochondrial dysfunction in primary rat hepatocytes and human HepG2 cells [16].…”
Section: Apoptosismentioning
confidence: 99%
“…Moreover, the mechanisms involved in the liver toxicity of anti-diabetic drug troglitazone, include mitochondrial dysfunction, apoptosis, disruption of calcium hemostasis, oxidative stress, and ER stress [23]. Although the most important mechanism for sertaline-induced liver toxicity is mitochondrial dysfunction and apoptosis, ER stress was found to contribute to its liver toxicity [29]. Interestingly, certain antioxidants (butylated hydroxyanisole (BHA), TM2002, and Baicalein) were also shown to cause ER stress in liver [30].…”
Section: Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%